Improved cycling time trial performance after 6-days of heat acclimation - Chapman, P.; Heap, T.; Alexander, S.; Thompson, M. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
The aim of the present study was to determine cycling time trialling (TT) performance and plasma volume (PV) changes after a relatively short 6-day 1-hour/day acclimation period in a warm-humid environment. Five competitive cyclists (age: 29.4±7.7yrs, VO2max: 4.78±1.01 l/min) cycled TT based on a workload equivalent to 85% VO2max for 15 minutes after a 1hr cycle before and after 6 days of heat acclimation in 30°C, 65%rh. Power output (PO), rectal temperature (Trec) and PV via CO-rebreathing technique were measured. Time to complete TT decreased significantly (939±193 vs. 773±132 seconds pre and post respectively, means±SD, p=0.01). Average TT PO increased significantly (286±55 vs. 334±61 watts, p=0.01). Average heart rate (HR) (177±12 vs. 177±13, p=0.93) was not significantly different. PV increased significantly by 9.3% (p<0.01). Trec was significantly lower at the end of the 1hr ride after heat acclimation (39.4±0.6 vs. 38.6±0.4, p=0.03) but was not significantly different after TT (39.7±0.7 vs. 39.5±0.4, p=0.2). Just 6 days of heat acclimation produced a 14.3% improvement in TT average PO whilst maintaining the same HR. A 9.3% increase in PV would have improved filling pressure to the heart, increased stroke volume and cardiac output making more blood available for convective heat loss. This is reflected in the lower Trec after 1hr cycling post heat acclimation. The improved performance may be put down to a lower core temperature at the beginning of TT and/or improved blood flow to the muscle.